The Concept of Heat Transfer measured by Cognitive Domain Assessment Instruments - Ni Kadek Yuniasih; Kadek Yudiana; I Gusti Ngurah Japa (Universitas Pendidikan Ganesha, 2021)
The lack of availability in assessment instruments used and unmet cognitive levels of C3-C6 resulted in poor quality assessments. This study aims to develop cognitive domain assessment instruments on the concept of heat transfer material in grade V elementary school. This research was development research that used 4D models (Four-D models) to define, design, develop, and disseminate. The subject of study was the assessment instrument of the cognitive realm with the object of research, that was the instrument quality. Measurement of the validity of the content was done on two experts/judges using the non-test method and instruments of the expert validity sheet. Instrument quality measurement was conducted with field trials of 106 students using multiple-choice objective test instruments. The content validity data obtained were analyzed with the Gregory formula, while the field test result data analyzed the validity of the grain, reliability, different power, and difficulty level.Â The results showed that the validity of the content obtained by 0.97 (very high) with the test results of the item's validity got 30 points of the question was declared valid. The instrument reliability index was developed by 0.85 (very high). The average coefficient of different power obtained is 0.51 (good) with a test device difficulty of 0.52 (medium). The result demonstrated cognitive domain assessment instruments that were developed feasible and can be used in conducting learning assessments in the cognitive realm.